1976
DOI: 10.1007/bf00219606
|View full text |Cite
|
Sign up to set email alerts
|

Hypothalamus and cytodifferentiation of the foetal pituitary gland

Abstract: To investigate whether the hypothalamus is involved in the cytodifferentiation of the anterior pituitary gland, rat foetuses were encephalectomized in utero on day 16 of pregnancy. Pituitary sections from encephalectomized and normal littermate foetuses were studied on day 21 with the immunofluorescence technique using antibodies anti alpha-MSH, anti beta-MSH, anti alpha-(17-39) ACTH and anti beta-(1-24) ACTH. On day 16, only the anti beta-MSH revealed a few cells in the pars distalis but not in the pars inter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
10
0

Year Published

1980
1980
2008
2008

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 33 publications
(12 citation statements)
references
References 9 publications
2
10
0
Order By: Relevance
“…However, a sparse opioid binding has been shown in the anterior pituitary gland (28) and opioids were not found to affect the release of ACTH from the pituitary in vivo (29). Moreover, we have previously reported that the hypothalamic content of CRF increases drastically in the developing rat from day 17 of gestation to week 4 post-partum (30), consistent with the hypothalamic control of the corticostimulating function of the pituitary gland as early as day 19 of gestation (3,31). Thus, morphine-induced activation of hypophysial±adrenocortical activity in the neonate probably occurs via the release of CRF.…”
Section: Discussionsupporting
confidence: 53%
“…However, a sparse opioid binding has been shown in the anterior pituitary gland (28) and opioids were not found to affect the release of ACTH from the pituitary in vivo (29). Moreover, we have previously reported that the hypothalamic content of CRF increases drastically in the developing rat from day 17 of gestation to week 4 post-partum (30), consistent with the hypothalamic control of the corticostimulating function of the pituitary gland as early as day 19 of gestation (3,31). Thus, morphine-induced activation of hypophysial±adrenocortical activity in the neonate probably occurs via the release of CRF.…”
Section: Discussionsupporting
confidence: 53%
“…Chatelain et al (1977), however, observed immunohistochemically the first PRL cells in the fetal rats on Day 21 and the reaction strength was very weak until Day 4 post partum. Watanabe and Daikoku (1979) failed to immunohistochemically detect PRL cells in the pituitarties of fetal rats.…”
Section: Discussionmentioning
confidence: 89%
“…It has been suggested that hypothalamic release factors could have an influence on this process [49][50][51][52]; nevertheless, embryonic pituitary cells can differentiate to LH-secreting cells in the absence of these factors [53]. In addition, extra-hypothalamic factors could have an influence on cell differentiation in the adenohypophysis; for instance, it is known that glucocorticoids stimulate differentiation of GH and PRL cells in vitro [54,55] and insulin seems to induce gonadotropic differentiation in cultures of embryonic rat adenohypophyseal cells [56].…”
Section: Could Il-1b and Il-6 Have An Influence On Hormonal Release Amentioning
confidence: 99%